2005
DOI: 10.1158/1541-7786.mcr-04-0166
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Ring Finger Protein 11

Abstract: Ring finger proteins serve many vital functions within the cell. We have identified RNF11, a novel 154-amino acid ring finger -containing protein, which is elevated in breast cancer. Within its ring finger domain, RNF11 contains an AKT phosphorylation site (T135) that is situated within a 14-3-3 binding domain. In WM239 cells with constitutively active AKT, RNF11 exhibits seven distinct phosphopeptides as measured using two-dimensional phosphopeptide mapping. Upon inhibition of the AKT pathway or mutation of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…Phosphorylation has far reaching consequences for the modified proteins, amoung them are conformational changes which effect substrate affinity and specificity [28,29]. It had been previously demonstrated that BCA2 was phosphorylated in the presence of AKT [8]. Here, we showed that BCA2 was more stable when co-expressed with constitutively active AKT as opposed to kinase-dead AKT.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Phosphorylation has far reaching consequences for the modified proteins, amoung them are conformational changes which effect substrate affinity and specificity [28,29]. It had been previously demonstrated that BCA2 was phosphorylated in the presence of AKT [8]. Here, we showed that BCA2 was more stable when co-expressed with constitutively active AKT as opposed to kinase-dead AKT.…”
Section: Discussionmentioning
confidence: 57%
“…BCA2 was shown to be phosphorylated in the AKT domain [8]. To investigate the role of phosphorylation on BCA2 stability, HEK293T cells were co-transfected with a constitutively active variant of AKT or a kinase-dead AKT mutant, along with FLAG-tagged BCA2 (Figure 5A, lanes 1 and 2) or the S132, 133A mutant which abolished AKT phosphorylation (Figure 5A, lanes 3 and 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AKT is a serine/threonine kinase that regulates a diverse array of cellular functions. It has been demonstrated that AKT phosphorylates Rabring7/BCA2 within the AKT phosphorylation site located between the BZF and the RING-H2 zinc fingers [27]. Two Rabring7/BCA2 copies are usually detected in vertebrates [19].…”
Section: Resultsmentioning
confidence: 99%